Determination of Maritime Safety in Indonesia: Analysis of Maritime Competence, Maritime Safety Management and Maritime Regulation - Nur Zaeni; Neng Sri Komala; Uti Indrawati Lestari; Abdullah Ade Suryobuwono (International Journal of Economics and Management Sciences, 2026)
This study aims to analyze the influence of maritime competence, maritime safety management, and maritime regulations on maritime safety in Indonesia. The approach used in this literature review is descriptive qualitative. Data collection techniques include literature studies or reviews of relevant previous articles published between 2021 and 2026. The technique used in this literature review is Comparative Analysis. The data used in this descriptive qualitative approach comes from previous research relevant to this study and is sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Web of Science, Sinta Journal 2-5, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books. The results of the study indicate that: 1) Maritime competence influences maritime safety in Indonesia; 2) Maritime safety management influences maritime safety in Indonesia; and 3) Maritime regulations influence maritime safety in Indonesia. The study concludes that a combined approach to enhancing maritime competence, management practices, and regulatory frameworks is critical in improving maritime safety in the region.